Aldehyde Dehydrogenase 2 Mediates Alcohol‐Induced Colorectal Cancer Immune Escape through Stabilizing PD‐L1 Expression. Issue 10 (24th March 2021) - Zhang, Hong; Xia, Yuhui; Wang, Fang; Luo, Min; Yang, Ke; Liang, Shaobo; An, Sainan; Wu, Shaocong; Yang, Chuan; Chen, Da; Xu, Meng; Cai, Muyan; et al.
Abstract: Despite the great success of immunotherapy in a small subset of cancer patients, most colorectal cancer (CRC) patients do not respond to programmed cell death receptor 1 (PD‐1) blockade immunotherapy. There is an urgent medical need to elucidate how cancer cells evade immune response and to develop novel means to boost the efficacy of immune checkpoint inhibitors. In this study, alcohol induces ligand programmed cell death receptor 1 (PD‐L1) expression of CRC cells in vitro and in vivo. Alcohol exposure is shown to induce aldehyde dehydrogenase 2 (ALDH2) expression that is a crucial enzyme involved in alcohol metabolism, and low level of lymphocytes infiltration in the murine CRC model and patients. Intriguingly, ALDH2 and PD‐L1 protein expression are positively correlated in tumor tissues from the CRC patients. Mechanistically, ALDH2 stabilizes PD‐L1 protein expression by physically interacting with the intracellular segment of PD‐L1 and inhibiting its proteasome‐dependent degradation mediated by an E3 ubiquitin ligase Speckle Type POZ Protein (SPOP). Importantly, inhibition of ALDH2 reduces PD‐L1 protein in CRC cells and promotes tumor‐infiltrating T cells (TILs) infiltration, presumably leading to the significant potentiation of anti‐PD‐1 antibody efficacy in a mouse CT26 CRC model. The findings highlight a crucial role played by ALDH2 to facilitate alcohol‐mediated tumor escape from immunity surveillance and promote tumor progression. Abstract : Aldehyde dehydrogenase 2 (ALDH2) promotes alcohol‐mediated immune escape through stabilizing ligand programmed cell death receptor 1 (PD‐L1) protein expression by interacting with the intracellular segment of PD‐L1, thereby inhibiting its ubiquitination mediated by Speckle Type POZ Protein (SPOP). Silencing of ALDH2 significantly sensitizes tumors to PD‐1 blockade therapy.